Cerebrovascular regulation in patients with active tumors and an acute ischemic stroke: a retrospective analysis - Lakatos, Lehel-Barna; Bolognese, Manuel; Oesterreich, Mareike; Müller, Martin; Karwacki, Grzegorz Marek (Frontiers in Physiology, 2024)
IntroductionIschemic stroke in patients with a systemic tumor disease or cancer not in remission (active tumors) is less well understood. Some aspects of such paraneoplastic strokes remind on a generalized cerebrovascular disorder. We hypothesized that cerebrovascular regulation in active tumor patients with a stroke is different from other patients with stroke who have no active tumor disease.MethodsWithin the first 72 h after the acute ischemic stroke, cerebral blood flow regulation was analyzed by means of transfer function analysis between middle cerebral artery blood flow velocity and blood pressure with estimation of coherence, gain and phase in the very low (0.02–0.07 Hz), low (0.07–0.20 Hz) and high frequencies (0.20–0.5 Hz) in four stroke groups: active tumors, inactive tumors (untreated and in remission), hypertensive lacunar stroke (LS), and non-hypertensive embolic stroke (NHES).ResultsThe 4 groups did not differ regarding age, sex distribution, and brain infarct size on magnet resonance imaging Between the four stroke groups, phase was not different in any frequency range in both hemispheres. Gain was highest (either significant or by trend) in the active tumor group in the HF range in comparison to all other stroke subgroups, it was also higher in the LF range in the stroke affected hemisphere when compared to the LS group. The HF gain findings were independent of end-tidal CO2 levels but exhibited some dependency of coherence.DiscussionThe high gain can be interpreted as a generalized high vascular resistance. The cerebrovascular regulation in active tumor patients seems to exhibit some analogy to hypertensive patients with lacunar stroke.Clinical Trial Registrationclinicaltrials.gov, identifier NCT04611672.